ENT 530 Social Media Portfolio: 1ms.Co / Muhammad Na'im Sallehudin - Sallehudin, Muhammad Na'im (2021)
1ms.Co is an online operating company that sells hipster clothing, including oversized shirts, Korean-style shirts, pants, shirts, and socks. It is an online business that is a dropship under a local brand owner, Gulfbox. This company also selling items with a pre-order system. 1ms.Co works for all transactional processes through various platforms such as Facebook, Instagram, and WhatsApp. In addition, 1ms.Co can contact customers on any platform because we are not like other shops that only answer Whatsapp. Although 1ms.Co is a full-service online business, it is mostly located in Seri Iskandar, Perak. The company also aims to give its consumers a fantastic experience. We serve our consumers at an affordable price only with the best fabric and high-quality items. We also emphasize the enjoyment and convenience of our consumers. Our objective is therefore to make our customers comfortable and delighted with their style. Our products come in different attractive and stylish styles, some of which are printed, some have strip patterns, and many more. 1ms.Co's plan comprises of promoting and advertising because we are merely a dropship company. We aspire to be one of Malaysia's most successful dropship companies. To attain our goal, we strive to enhance our business on a regular basis in order to maintain a healthy rivalry with other companies in the same fashion and apparel industry as us.